Pengaruh Priming Auksin Terhadap Perkecambahan Benih Padi Ir64 Pada Cekaman Salinitas - Anggraini Anggraini; Muftia Nadhra; Yoana Marizky Siregar; Violita Violita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Salinity is a major abiotic constraint that limits rice establishment, particularly during germination when seedlings are physiologically vulnerable. This study investigated the effect of auxin priming on germination performance and early seedling growth of IR64 rice exposed to 100 mM NaCl, and identified the most effective auxin concentration. The experiment was conducted using a Completely Randomized Design with five treatments: non-primed seeds and auxin priming at concentrations of 0, 25, 50, and 100 ppm, each with three replications. Statistical analysis was performed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test at the 5% significance level. Parameters observed included germination percentage and rate, root and plumule length, total seedling length, vigor index, fresh and dry weight, and lipid peroxidation. Auxin priming significantly enhanced germination rate, seedling growth, vigor index, and biomass accumulation, while reducing lipid peroxidation under saline conditions. Among the treatments, P3 exhibited the most consistent improvement under salinity stress, whereas P1 showed the highest overall growth under non-stress conditions. These findings indicate that appropriate auxin priming can improve the early physiological performance of rice seedlings under salt stress.